The Casa da Índia and the Emergence of a Science of Administration in the Portuguese Empire - Xavier, Ângela Barreto (2018)
The role played by archives in the making of a Portuguese science of imperial administration is scarcely known. Systematic research is still lacking on what literature suggests was a critical dimension in the management of the empire. By focusing on the Casa da Índia’s activities of production, record-keeping and retrieving of information and knowledge, this study intends to contribute to a better understanding of the links between empire and Portuguese early-modern archival experiences. For more than a century, the Casa da Índia was the institution responsible for the circulation and storage of commodities, information and people within the Portuguese empire, as well as the payment of duties and taxes. What challenges did territorial expansion entail for the Portuguese monarchy, and, in particular, for its archival organization and practices? How did the Casa da Índia register these imperial dynamics? Did its archive materialize the Empire at home? Finally, was its archive relevant to the emergence of a Portuguese science of imperial administration?